(untitled) (American Journal of Technology and Applied Sciences, 2025)
The concept of the smart city has emerged as a dominant paradigm in twenty-first-century urban planning, where digital design, information technologies, and data-driven decision-making are integrated to create cities that are more sustainable, efficient, and responsive to the needs of their inhabitants. This research explores the smart city as both a theoretical framework and a practical approach to urban development, focusing on the role of digital design in planning processes, governance structures, and infrastructural systems. By reviewing global practices and contextualizing them within the framework of Uzbekistan’s urban transformation, this study highlights the ways in which tools such as Geographic Information Systems (GIS), Building Information Modeling (BIM), Internet of Things (IoT) networks, and digital twin technologies are reshaping the way cities are designed, managed, and experienced. The analysis demonstrates that smart cities are not merely technological constructs but also socio-cultural systems where sustainability, inclusivity, and resilience are as significant as efficiency and productivity. Results drawn from global case studies in Singapore, Songdo, Amsterdam, and Dubai indicate that digital design facilitates improved energy management, transport efficiency, environmental monitoring, and citizen participation. At the same time, critical examination reveals challenges related to data privacy, cyber security, technological dependency, and socio-economic inequality, which demand careful regulation and ethical frameworks. For Uzbekistan, where rapid urbanization intersects with historic architectural heritage, smart city planning offers both opportunities and challenges: it provides pathways for optimizing infrastructure, improving governance, and enhancing quality of life, while requiring adaptation to local cultural and social contexts. This article concludes that smart city development, underpinned by digital design, represents not only a technological advancement but also a transformative cultural and political project that redefines urban life in the digital age.